Convergent evolution of elaborate nests as structural defences in birds. Issue 1989 (21st December 2022) - Street, Sally E.; Jaques, Robert; De Silva, Thilina N.
Abstract : The pendent nests of some weaverbird and icterid species are among the most complex structures built by any animal, but why they have evolved remains to be explained. The precarious attachments and extended entrance tunnels characteristic of these nests are widely speculated to act as structural defences against invasion by nest predators, particularly tree-climbing snakes, but this hypothesis has yet to be systematically tested. We use phylogenetic comparative methods to investigate the relationship between nest structure and developmental period length, a proxy for offspring mortality, in weaverbirds (Ploceidae) and icterids (Icteridae), two bird families in which highly elaborate pendent nests have independently evolved. We find that more elaborate nests, particularly those with entrance tunnels, are associated with longer developmental periods in both families. This finding is robust to potentially confounding effects of body mass, phylogenetic relationships, nest location and latitude. Our results are consistent with the hypothesis that elaborate nest structures in birds can function as structural defences, resulting in lower offspring mortality and slower development. More generally, our findings suggest that constructing complex, protective structures may buffer against environmental hazards, reducing extrinsic mortality and contributing to the evolution of slower life histories in diverse animal lineages, even humans.